Anterior Uveitis as an Initial Manifestation of Polymyalgia Rheumatica - Hiromasa Tsuda; Kozue Tanaka; Shuji Kishida (Case Reports in Medicine)
A 74-year-old woman without contributory medical history presented with acute iridocyclitis in the right eye. Although the iridocyclitis disappeared within two weeks under topical steroid, she complained of acute progressing bilateral shoulder pain and morning stiffness of upper extremities. She was diagnosed as having polymyalgia rheumatica (PMR), and iridocyclitis was considered as its related manifestation. PMR and giant cell arteritis (GCA) are closely related conditions and frequently occur together. GCA with uveitis has been rarely noted. However, ocular symptoms in PMR have not been previously mentioned. This is a first reported case of PMR presented with uveitis, without a complication of GCA. This anterior uveitis might be caused by ischemia of the posterior ciliary arteries and their branches.